Can taxes raise output and reduce inequality? The case of lobbying - Klaus Prettner; Davud Rostam-Afschar (Scottish Journal of Political Economy, 2020)
One of the key institutional elements for reducing inequality is the tax and transfer system. However, economists and policymakers usually view high taxes as detrimental to economic growth. We isolate one important mechanism by which higher taxes reduce inequality and raise per capita gross domestic product (GDP) at the same time. This mechanism operates in the presence of unproductive lobbying. Higher taxes induce a reallocation from lobbying toward production. This raises overall output and reduces the consumption gap between those who benefit from lobbying and those who bear its negative effects.
Keywords: 330; equity-efficiency trade-off; inequality; lobbying; rent-seeking; taxation